Multi–dimensional digital human models for ergonomic analysis based on natural data representations. (28th January 2015) - Moes, Niels C.C.M.
Digital human models are often used for ergonomic analysis of product designs, before physical prototypes are available. However, existing digital human models cannot be used to simultaneously: 1) consider the tissue loads and the physiological effects of the tissue loads; 2) optimise the product properties. This paper develops multi–dimensional digital human models for ergonomic analysis based on natural data representations, which include anatomy, morphology, behaviour, physiology, tissue, and posture data representations. The results show that the multi–dimensional digital human models can be used to: 1) accelerate the design process; 2) assess mechanical and physiological loads inside the body and in the contact area between the body and the product; 3) optimise the quality of the product; 4) reduce the number of user trials needed to create the product.